The cultivation of conformity: towards a general theory of internal secularisation - Dandelion, Pink (Routledge, Taylor & Francis Group, 2019)
Theoretical context: the conundrum facing religious groups -- Organisational types and the inclination to conform -- Secularisation, secularism, rights and recruitment -- Theoretical complexities : religion and "the world" -- The history of the hedge -- Quakers as citizens and outlaws -- Modelling turbulence -- New theory: a future of religiosity -- Quaker culture and non-doctrinal assimilation -- Internal secularisation: elements and agency -- References.